Evaluation of the Limping Child: Current Concept Review - Burns, Jessica; Mubarak, Scott (Journal of the Pediatric Orthopaedic Society of North America, 2020)
Evaluation of the etiology of a younger child (age <5) with gait disturbance or refusal to walk is a critical skill for the orthopedic surgeon. The common causes are trauma and infection, which can often be delineated with a detailed history. Prompt diagnosis is critical to distinguish orthopedic emergencies from relatively benign processes and chronic problems such as arthritis. Physical examination should utilize the parent’s lap to keep the child comfortable. Examination should include evaluation of gait, supine and prone hip examination, and the crawl test. There are six radiographic views of the lower extremities that can assist in the diagnosis. In conjunction with the detailed history, thorough physical exam, and radiographs the orthopedic surgeon can determine the need for laboratory tests and other imaging.